(untitled) (Archive of Conferences, 2021)
In this article, the symbolic symbols in the works of the Uzbek writer Nemat Arslan are revealed through various analyzes. In particular, the concept of modern literature today is considered to be the pursuit of innovation, the creation of unusual methods and plots. This also leads to a different depiction of emotional experiences.Uzbek literature